Greenhouse gas emissions and strategies for mitigation: opportunities in agriculture and energy sector - Parihar, Arun K. (Kansas State University, 2009)
The impact of human activities on the atmosphere and the accompanying risks of long-term global climate change are by now familiar topics to many people. Although most of the increase in greenhouse gas (GHG) concentrations is due to carbon dioxide (CO2) emissions from fossil fuels, globally about one-third of the total human-induced warming effect due to GHGs comes from agriculture and land-use. This report provides a brief review of greenhouse effects and impacts on climate, human health and environment. The sources of emissions of greenhouse gases due to human activities, both current estimates and future projections, have been included. The report further discusses possible options for mitigation of greenhouse gases. The report also discusses the role agriculture can play towards mitigation of greenhouse gases as many agricultural processes such as anaerobic digestion, manure gasification; carbon sequestration etc. can help reduce or offset greenhouse gas emissions. Capture and sequestration of CO2 released as a result of burning fossil fuel in power plants, energy and other industries is gaining widespread interest as a potential method of controlling greenhouse gas emissions. Various technologies such as amine (MEA)-based CO2 absorption system for post-combustion flue gas applications have been developed, and can be integrated with existing plant operations. Removal of SO2 by using amine-based carbon capture system offers additional benefit. Efforts are underway to develop a broader suite of carbon capture and sequestration technologies for more comprehensive assessments in the context of multi-pollutant environmental management. Geologic formations and/ or possibly oceans can be used as sinks to store recovered CO2. In oil and gas exploration industry CO2 may be injected in producing or abandoned reservoirs which will not only help in maintaining the reservoir pressure (which improves overall field exploitation) but in some cases even leads to enhanced oil recovery.
Keywords: Mitigation of Greenhouse Gases; Climate Change; Carbon Sequestration; Engineering, Chemical (0542); Engineering, Environmental (0775); Engineering, General (0537)